Leading Schools in Times of Covid-19: Building Resilience [Dirigir Escuelas en Tiempos de Covid-19: La Construcción de la Resiliencia] - Villalta-Paucar, M (Universidad Autonoma de Baja California, 2022)
The situation brought about by COVID-19 has transformed the way in which schools operate and the goals they have historically served. The objective of this research is to describe COVID-19 conditions that have an impact on the way contact in education is reflected upon and fostered, from the perspective of elementary school principals. Qualitative content analysis was conducted on in-depth interviews with principals from eight elementary schools in urban and rural areas in three regions of Chile. The results show that concern for content learning has given way to concern for students’ socio-emotional well-being, and that in a COVID-19 context schools work differently depending on the area, with rural schools drawing on and strengthening their collaborative relationship with the community, while urban schools have focused on efficient use of digital technology. © 2022,Revista Electronica de Investigacion Educativa. All Rights Reserved.